The impact of vitamin D supplementation as an adjuvant therapy on clinical outcomes in patients with severe atopic dermatitis: A randomized controlled trial - Noha O. Mansour; Amal Ahmed Mohamed; Maha Hussein; Eman Eldemiry; Aliaa Daifalla; Soha Hassanin; Nourelhuda Nassar; Doaa Ghaith; Eman Mohamed Salah (Wiley, 2020)
Abstract Vitamin D supplementation with standard treatment yielded positive clinical outcomes in mild and moderate atopic dermatitis; however, the potential benefit of vitamin D in severe cases remains unclear. This study aimed to evaluate the impact of vitamin D supplementation on response to standard treatment in pediatrics with severe atopic dermatitis. The patients were randomized to receive either vitamin D 3 1600 IU/day or placebo, plus baseline therapy of topical 1% hydrocortisone cream twice daily for 12 weeks. The primary endpoints were the change in mean Eczema Area and Severity Index (EASI) score at the end of the study and the mean percent change in EASI score from baseline to week 12. Eighty‐six subjects completed the study. The treated group achieved a significant higher level of 25 hydroxy vitamin D (P < .001) compared to control group at week 12. The mean EASI score was significantly lower in the treatment group compared to placebo group (P = .035). The percent change in EASI score from baseline differed significantly between the supplementation (56.44 ± 29.33) and placebo (42.09 ± 19.22) groups after intervention (P = .039). Vitamin D supplementation could be an effective adjuvant treatment that improves the clinical outcomes in severe atopic dermatitis.